Phytochemical and in Vivo Biological Studies of Tanaecium Bilabiatum (Sprague) L.G. Lohmann (Bangladesh Journal of Botany, 2023)
Phytochemical analysis of Tanaecium bilabiatum leaf led to the isolation and identification of salacinin C, daturadiol and a mixture of triterpenes, α-amyrin and β-amyrin. Besides chemical analysis, the methanol extract of T. bilabiatum leaf, METBL was evaluated for analgesic, anti-diarrheal and hypoglycemic potential in mice model. For analgesic activity test by tail immersion technique, the extract significantly extended the percent elongation time of thermal nociception. METBL (400 mg/kg bw) also established the highest inhibition of formalin-induced abdominal writhing (69.39%) in mice, which was comparable with the standard aspirin (75.51%). Likewise, dose-dependent antidiarrheal activity was observed in this test. After oral administration, METBL demonstrated maximum inhibition (40.93%) of castor oil-induced diarrhea in mice. In oral glucose tolerance test, the plant extract produced significant (p < 0.05) hypoglycemic activity. Therefore, it is concluded that T. bilabiatum is a promising source of bioactive compounds with analgesic, antidiarrheal and hypoglycemic potential. Bangladesh J. Bot. 52(1): 119-127, 2023 (March)